2003
DOI: 10.1001/archneur.60.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Loss Is Greater in the Locus Coeruleus Than Nucleus Basalis and Substantia Nigra in Alzheimer and Parkinson Diseases

Abstract: For both AD and PD the greatest neuronal loss was found in the LC. In AD, neuronal loss was most severe and best correlated with the duration of illness in the LC, rather than in NB as traditionally expected. Correlations between neuronal loss in the LC and NB (but not SN) in both PD and AD suggest that the former 2 nuclei may share common pathogenetic susceptibilities. Given the prominent loss of neurons in the LC, detection and treatment of noradrenergic deficiencies warrant attention in both AD and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
638
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 873 publications
(690 citation statements)
references
References 34 publications
23
638
0
8
Order By: Relevance
“…However, studies of post-mortem PD brains have shown that not only DA neurons in the SN but also noradrenaline (NA) neurons in the locus coeruleus (LC) degenerate, and that NA neurodegeneration may be as profound, and also precede, degeneration of midbrain DA neurons (German et al, 1992;Patt and Gerhard, 1993;Zarow et al, 2003). The early involvement of the NA system is also in line with the caudal-to-rostral disease progression predicted by the model proposed by Braak et al (Braak et al, 2003;Hawkes et al, 2007Hawkes et al, , 2009).…”
Section: Introductionmentioning
confidence: 73%
“…However, studies of post-mortem PD brains have shown that not only DA neurons in the SN but also noradrenaline (NA) neurons in the locus coeruleus (LC) degenerate, and that NA neurodegeneration may be as profound, and also precede, degeneration of midbrain DA neurons (German et al, 1992;Patt and Gerhard, 1993;Zarow et al, 2003). The early involvement of the NA system is also in line with the caudal-to-rostral disease progression predicted by the model proposed by Braak et al (Braak et al, 2003;Hawkes et al, 2007Hawkes et al, , 2009).…”
Section: Introductionmentioning
confidence: 73%
“…Indeed, drugs that affect these neuromodulators substantially reduce the benefits of VNS therapy in tinnitus patients [45], indicating that these neuromodulatory pathways are necessary for the effects of VNS. Several diseases affect cell number and function in these neuromodulatory systems, including Alzheimer disease, PD, chronic alcoholism, Down syndrome, TBI, and PTSD [118][119][120][121][122][123][124][125][126]. Comorbidity with these and other diseases that impair neuromodulatory function may limit the effects of VNS.…”
Section: Challenges For Translating Vns Therapies Into Clinical Practmentioning
confidence: 99%
“…Although neuritic plaques and their amyloid components continue to play a critical role in the diagnosis of Alzheimer's disease (AD), semi-quantitative studies in groups of normalaged and AD patients have reported that these so-called neuropathological markers of AD also occur to varying degrees in cortical tissue during normal aging, and that their accumulation does not directly correlate with the progression of dementia (Mirra et al 1993;McKeel et al 2004;Tiraboschi et al 2004). Stereological and neurochemical studies of brain tissue from patients with AD have confirmed widespread astrocytosis and microgliosis in cortical brain regions and significant reductions in neurotransmitter-specific subcortical nuclei, including the locus coeruleus (LC) and dorsal raphe (DR), and diminished concentrations in their cortical projections of corresponding monoamine neurotransmitters, norepinephrine (NE) and 5-hydroxytrptamine (5-HT); in contrast, these parameters remain relatively stable in brains of persons that undergo normal (non-demented) brain aging (Aletrino et al 1992;Mouton et al 1994;Storga et al 1996;Zarow et al 2003;Tuppo and Arias 2005). The strongest correlations with dementia severity have been reported in the loss of cortical volume (atrophy), observed by either ante-mortem or post-mortem analyses, and the reduction in cortical synapses (de la Monte 1989;DeKosky and Scheff 1990;Terry et al 1991;Convit et al 1993;Jobst et al 1994;Stout et al 1996;Mouton et al 1998;Zarow et al 2003;de Leon et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Stereological and neurochemical studies of brain tissue from patients with AD have confirmed widespread astrocytosis and microgliosis in cortical brain regions and significant reductions in neurotransmitter-specific subcortical nuclei, including the locus coeruleus (LC) and dorsal raphe (DR), and diminished concentrations in their cortical projections of corresponding monoamine neurotransmitters, norepinephrine (NE) and 5-hydroxytrptamine (5-HT); in contrast, these parameters remain relatively stable in brains of persons that undergo normal (non-demented) brain aging (Aletrino et al 1992;Mouton et al 1994;Storga et al 1996;Zarow et al 2003;Tuppo and Arias 2005). The strongest correlations with dementia severity have been reported in the loss of cortical volume (atrophy), observed by either ante-mortem or post-mortem analyses, and the reduction in cortical synapses (de la Monte 1989;DeKosky and Scheff 1990;Terry et al 1991;Convit et al 1993;Jobst et al 1994;Stout et al 1996;Mouton et al 1998;Zarow et al 2003;de Leon et al 2004). Thus, the evidence to date indicates that, while the diagnosis of AD depends heavily on the presence of amyloid plaques in neocortical brain regions, the progression of AD dementia appears to correlate more closely with degeneration of subcortical neurotransmitter systems that project to cortex, cortical synapse loss, and reduction of cortical volumes.…”
Section: Introductionmentioning
confidence: 99%